Downregulation of Bim, a Proapoptotic Relative of Bcl-2, Is a Pivotal Step in Cytokine-Initiated Survival Signaling in Murine Hematopoietic Progenitors - Shinjyo, Tetsuharu (American Society for Microbiology, 2001)
Two distinct signaling pathways regulate the survival of interleukin-3 (IL-3)-dependent hematopoietic progenitors. One originates from the membrane-proximal portion of the cytoplasmic domain of the IL-3 receptor (βc chain), which is shared by IL-3 and granulocyte-macrophage colony-stimulating factor and is involved in the regulation of Bcl-x(L) through activation of STAT5. The other pathway emanates from the distal region of the βc chain and overlaps with downstream signals from constitutively active Ras proteins. Although the latter pathway is indispensable for cell survival, its downstream targets remain largely undefined. Here we show that the expression of Bim, a member of the BH3-only subfamily of cell death activators, is downregulated by IL-3 signaling through either of two major Ras pathways: Raf/mitogen-activated protein kinase and the phosphatidylinositol 3-kinase/mammalian target of rapamycin. Akt/phosphokinase B does not appear to play a significant role in this regulatory cascade. Bim downregulation has important implications for cell survival, since enforced expression of this death activator at levels equivalent to those induced by cytokine withdrawal led to apoptosis even in the presence of IL-3. We conclude that Bim is a pivotal molecule in cytokine regulation of hematopoietic cell survival.